"Inherently Chiral" Ionic‐Liquid Media: Effective Chiral Electroanalysis on Achiral Electrodes. (18th January 2017) - Rizzo, Simona; Arnaboldi, Serena; Mihali, Voichita; Cirilli, Roberto; Forni, Alessandra; Gennaro, Armando; Isse, Abdirisak Ahmed; Pierini, Marco; Mussini, Patrizia Romana; Sannicolò, Francesco
Abstract: To achieve enantioselective electroanalysis either chiral electrodes or chiral media are needed. High enantiodiscrimination properties can be granted by the "inherent chirality" strategy of developing molecular materials in which the stereogenic element responsible for chirality coincides with the molecular portion responsible for their specific properties, an approach recently yielding outstanding performances as electrode surfaces. Inherently chiral ionic liquids (ICILs) have now been prepared starting from atropisomeric 3, 3′‐bicollidine, synthesized from inexpensive reagents, resolved into antipodes without need of chiral HPLC and converted into long‐chain dialkyl salts with melting points below room temperature. Both the new ICILs and shorter family terms, solid at room temperature, employed as low‐concentration additives in achiral ILs, afford impressive enantioselection for the enantiomers of different probes on achiral electrodes, regularly increasing with additive concentration.